If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(m + -2) + 2(3m + 2) = 0 Reorder the terms: 4(-2 + m) + 2(3m + 2) = 0 (-2 * 4 + m * 4) + 2(3m + 2) = 0 (-8 + 4m) + 2(3m + 2) = 0 Reorder the terms: -8 + 4m + 2(2 + 3m) = 0 -8 + 4m + (2 * 2 + 3m * 2) = 0 -8 + 4m + (4 + 6m) = 0 Reorder the terms: -8 + 4 + 4m + 6m = 0 Combine like terms: -8 + 4 = -4 -4 + 4m + 6m = 0 Combine like terms: 4m + 6m = 10m -4 + 10m = 0 Solving -4 + 10m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 10m = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 10m = 0 + 4 10m = 0 + 4 Combine like terms: 0 + 4 = 4 10m = 4 Divide each side by '10'. m = 0.4 Simplifying m = 0.4
| 8x-16=4x-4 | | 525+0.21x=850 | | 11x+5=4x+9 | | x+6=40 | | 13(4x-7)=13 | | 8(3x+6)=96 | | 2(x+7)=56 | | s^2+s+4=0 | | 71-6x=35 | | 22+4x=50 | | y^2-4= | | 5x-73=27 | | 2Y^3-Y+3X-2=0 | | 6x+29=13x+41 | | s^2-s+4=0 | | (6x-7)+9x=68 | | 10x-117=5x-7 | | 8x^7y(5x^6y^2-6x^2+4y^3)= | | 5(2y+4)= | | -2+3(x-9)-2(x+3)=0 | | 2z^2+40=-8z | | 4+x=117 | | p+4p=60 | | 5x^2+30x-10=0 | | 3n+5=n-8 | | 3y(2y-4)=16 | | 3y(2y-4)=21 | | log*x^2-log*x=log*100 | | 3x-8+8=34 | | 4x+12=8x-36 | | -3x+x=-21 | | x^3+x^2-5x+3=0 |